Media Pembelajaran Teknik Informasi dan Komunikasi Untuk Kelas VIII Sekolah Menengah Pertama Negeri 2 Tawangmangu - Sri Agustinawati - Universitas Surakarta; Bambang Eka Purnama - STMIK Nusa Mandiri (Universitas Bina Sarana Informatika, 2017)
ABSTRACT – Teaching system using interactive media is one way to deliver learning materials. Very precise delivery of material to assist students in understanding the material presented. Student learning system in SMP Negeri 2 Tawangmangu particularly on the subjects of information and communication technology is still less than the maximum, because the education system is still simple example student worksheets and books - other companion books. To overcome this it is necessary to study media can facilitate teachers in delivering learning material.By using media pemebelajaran expected students to quickly grasp the information and communication technology lessons and facilitate teachers in presenting the material to students. In this study the authors used methods of literature, interview, analysis, design, construct, test the system.Hopefully with this learning medium of teaching and learning can help students in SMP Negeri 2 Tawangmangu. Further expected learning media can be used by teachers of information and communication technology to deliver learning material and can facilitate students in receiving the materialKeywords: Multimedia Learning